PTU-236 Surgical site infection (SSI) rates in colorectal surgery: room for improvement. (22nd June 2015) - Docherty, J
Abstract : Introduction: SSI in colorectal surgery is a major cause of morbidity and is poorly recorded in clinical practice. We had a high rate of wound infection in our unit and therefore over a four year period we worked as a multidisciplinary group which included colorectal surgeons, infection control / surveillance nurses, microbiologists, theatre nurses and ward nurses to reduce our SSI rate in major elective colorectal surgery. We envisaged that we could reduce our wound infection rate but recognised that deep and organ space infection would remain unchanged, as these are related to anastomotic failure, which would not be altered by this work. Our aim, therefore, was to use quality improvement methodology to change our SSI rates. Method: We formed a core team –the collaborative who met monthly. Using the model for improvement we set an aim- to reduce colorectal SSI in elective patients by 50% by June 2014. We looked at the evidence to determine changes we would make and we collected data weekly on all elective colorectal patients. Independent to the surgical team, infection surveillance staff monitored colorectal patients' wounds and identified patients with in hospital and readmission wound infections, within 30 days of surgery (using standard national definitions of SSI). Based on the available evidence we introduced several changes over this quality improvement project: designed dedicated data collection forms written pre-op advice to patients clippers used for immediate hair removal changed to 2% chlorhexedine skin preparation introduced specific closing trays and limited redraping standardised wound dressing and its management, reviewed prophylactic antibiotic cover standardised prophylactic antibiotics and ensured repeat administration in long procedures and where there was excessive blood loss ensured tight glyacemic control in diabetic patients and strove for normothermia Using the model for improvement ensured reliability of all of our processes in the work detailed above and enabled us to maintain success Results: Three of the four consultant colorectal surgeons were in post for the whole time period and all of their major elective colorectal patients are included. For the calendar years 2012 to 2014 our collective infection rates are shown in the Table 1 . We achieved our aim of reducing colorectal SSI by 50%. Conclusion: By engaging the multidisciplinary team and explaining what we wanted to achieve; we were able to consistently apply the evidence base and substantially lower wound infection rates in elective colorectal surgery. Our next priority in this work is ensure that all of the processes underpinning this reduction are reliable and will continue in perpetuity. Disclosure of interest: None Declared.